Global Epidemiology of Hepatitis B Virus (HBV) Infection - Hwang, MD, Elizabeth W.; Cheung, MD, Ramsey (North American Journal of Medicine and Science, 2011)
Hepatitis B virus (HBV), a DNA virus with a human-only reservoir, is a worldwide public health problem. Hepatitis B is transmitted through parenteral or mucosal exposure to infected blood and body fluids. The mode of transmission is usually vertical or horizontal in highly endemic areas early in life, resulting in a high chronicity rate. In low endemic countries, transmission is usually in adulthood with self-limiting infection in most. The prevalence of chronic HBV infection is highly variable, ranging from 0.1% in the United States to 20-30% in some Pacific Island nations. There are an estimated 360 million people who are chronically infected, of whom almost one million people die annually of HBV-related liver disease. Chronic hepatitis B is the major cause of hepatocellular carcinoma in the world. Safe and effective HBV vaccines have been available since 1982. The implementation of effective vaccination programs has resulted in a significant decrease in the incidence of chronic hepatitis B infection. Nevertheless, hepatitis B remains an important cause of morbidity and mortality among the chronic carriers worldwide. Understanding the epidemiology of the disease is essential in developing programs to prevent and treat this global infection.